The Incidence of Culture, Governance, and Economics on the Countries’ Development through an Analysis of Coupled Networks - Castaneda, Gonzalo; Chavez-Juarez, Florian (World Bank, Washington, DC, 2017)
This paper introduces an innovative methodology that combines industry level information (exports, HA 4-digits) with indicators at the country level, to analyze which social capabilities are important to explain the observed patterns of structural transformation. The authors consider several indicators to characterize three dimensions: cultural, governance, and economic, plus only one indicator (polity) for a political dimension. Through the use of the product space, a measure of density that identifies the proximity of non-developed products to the countries’ export profile, and a system of coupled networks where densities are adjusted in terms of social affinities, the authors find the following main results: (i) countries can be competitive in certain industries even if they do not have a high value in some of these indicators; (ii) the governance dimension is closely related on how the countries’ export profiles are positioned in the product space; and (iii) all of these dimensions, but not all the indicators, help explain the observed process of structural transformation and the widening of the gap between poor and rich countries.